Taxonomic position of Heissothignus and review of the species of Meschia (Hemiptera: Heteroptera: Meschiidae) - Malipatil, M. B.; Yeshwanth, H. M.; Kondorosy, Előd (Zootaxa, 2021)
The New Guinean genus Heissothignus Slater & Brailovsky, 2006 (Hemiptera: Heteroptera: Meschiidae) possesses several morphological characters unique to family Meschiidae but not occurring in Heterogastridae, confirming its placement within the family Meschiidae. A key to the genera of the family Meschiidae is presented. The two species of the genus Meschia Distant, 1910 recorded from the Indian subcontinent are reviewed, and the following new synonymy is proposed: M. pugnax Distant, 1910 = M. quadrimaculata Distant, 1910, syn. nov. A revised key to the species of Meschia is provided. New country and state records are provided for M. pugnax (India: Andhra Pradesh, Karnataka, Meghalaya, Rajasthan, Tamil Nadu and Uttarakhand), Meschia barrowensis Malipatil, 2014 (Australia: New South Wales) and Meschia zoui Gao & Malipatil, 2019 (Thailand).